Self-nudging toward physical activity: Scale development, validation, and workplace implications - Bakker, Arnold B.; Toyama, Hiroyuki; Yajima, Jumpei; Iwano, Suguru; Hietajärvi, Lauri; Upadyaya, Katja; Salmela‐Aro, Katariina (John Wiley & Sons, 2026)
This study uses nudging theory to develop and validate a measure for self-nudging toward physical activity. The research unfolds in three phases: (a) initial item development through interviews and literature review, (b) psychometric testing with Japanese employees (N = 1540), and (c) validity assessment in a longitudinal subsample (N = 716). Factor analyses confirm a reliable one-factor structure. The scale demonstrates content and predictive validity, showing positive relationships with physical activity, physical capacity (fitness and energy), well-being (workability, work engagement, and job satisfaction), and job performance; and negative relationships with strain (psychological distress, exhaustion, and occupational depression). Structural equation analyses show that self-nudging at Time 1 is positively related to well-being and negatively related to strain at Time 2 (3 months later) through increased physical capacity, with effects remaining significant after controlling for baseline measures. The findings contribute to our understanding of the associations among self-nudging, physical activity, and occupational well-being. The results have implications for both theoretical advancement in nudging research and practical applications in workplace health promotion.
Keywords: nudging theory; physical activity; self-nudging; self-regulation; work engagement; fi=Henkilöstöjohtaminen|en=Human Resource Management|